Professional Advancement and Performance of Amateur Baseball Players Selected in the Major League Baseball Draft With Previous Anterior Cruciate Ligament Reconstruction. Issue 3 (March 2020) - Porter, Anthony; Yang, Shawn; Chauhan, Aakash; Early, Samuel; Challa, Sravya; D'Angelo, John; Keefe, Daniel; Hoenecke, Heinz; Fronek, Jan
Background: The effect that an anterior cruciate ligament injury requiring reconstructive surgery has on the professional advancement and performance of amateur baseball players selected in the Major League Baseball draft is not known. Return to sports after anterior cruciate ligament reconstruction (ACLR) in professional athletes has been shown to be high, but mixed results with regard to performance and return to preinjury level have been demonstrated in other sports. Purpose: To (1) investigate the highest level of professional advancement among Major League Baseball draftees with a history of ACLR before entering the draft, (2) examine how much time these players spent on the disabled list (DL) and determine if it was related to the knee, and (3) compare the batting and pitching performance of these players against healthy matched controls. Study Design: Cohort study; Level of evidence, 3. Methods: Predraft medical records of all players selected in the Major League Baseball draft from 2004 to 2008 were reviewed. Players with a documented anterior cruciate ligament injury treated with ACLR before the draft were included. For each study player, 3 controls were identified. Data were accumulated from the time when players were drafted through the 2015 season. Outcome variables included highest professional level of advancement, DL time, and batting and pitching performance. Results: Forty draftees with a history of ACLR (22 pitchers, 18 position players) were identified and matched to 120 controls (66 pitchers, 54 position players). The difference in the highest level of professional advancement between the groups was not statistically significant ( P = .488). The mean total number of times and the mean total number of days on the DL were similar between the groups (1.83 vs 1.47, P = .297; 121.54 vs 109.62, P = .955); however, the mean number of times on the DL because of a knee injury was significantly different (0.28 vs 0.11, P = .004), as was the mean number of days on the DL because of a knee injury (17.36 vs 7.72, P = .009). Among pitchers, there were no differences in performance. Similarly, there were no differences among position players in batting performance. Conclusion: There was no difference between draftees with a history of ACLR and their controls in terms of advancement from the minor to the major leagues. Additionally, pitching and batting performance were similar. Although the 2 groups spent similar time on the DL, the ACLR group spent more time on the DL because of a knee injury than the control group.